Web e-Learning Component Analysis: A Metamodel - Narti Prihartini (Journal of Computers for Society, 2020)
Research focus on learning technologies currently classified into three main themes included pedagogical aspect, underpinning technology, and organizational issues. In particular, there is an expand research on how to explore learning technologies in order to support the communication and collaboration by increasing focus on relevant pedagogical and organizational issues. Concerns that appear in every research focus can be related to determine the specific component of web e-learning. Analysis of specific component then required to describe all aspects that support the web e-learning implementation. Final result from this analysis is initialization of web e-learning component in logical and technical along with it relations by proposed a web e-learning component metamodel.